Writing about Wolves: Using Ecocomposition Pedagogy to Teach Social Justice in a Theme-Based Composition Course - Michael S. Geary (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
Elements of ecocomposition are employed to construct a course that uses the relationship between wolves and humans as a social justice metaphor. Students explore how mythmaking leads to dire consequences for any population being exploited. This approach to teaching first year composition allows students to acquire new knowledge about conservationism while focusing on developing their critical reading, writing, and researching skills.